Deforestation and reforestation in Namibia : the global consequences of local contradictions - Kreike, Emmanuel, 1959- (Afrika-Studiecentrum series ;, 2010)
Descriptions of the late 1800s landscape in the Ovambo floodplain in north-central Namibia closely match the area's late 1900s appearance, suggesting that little change occurred between the pre-colonial baseline and the postcolonial outcome. Yet, paradoxically, colonial conquest, population pressure, biological invasions, new technology, and economic globalization caused both dramatic deforestation and reforestation in less than a century. The paradox stems from the fact that the prevailing global environmental models obscure and homogenize the process of environmental change: different and co.